Two novel alleles HLA‐DRB1*11:150 and HLA‐DRB1*14:145 identified in Saudi individuals. (12th June 2014) - Fakhoury, H. A.; Cereb, N.; Jawdat, D.; Al Jumah, M.; Alaskar, A. S.; Hajeer, A. H.
Summary Two new HLA‐ DRB1 alleles were identified by sequence‐based typing method (SBT) in 1100 participants in the Saudi Stem Cell Donor Registry. HLA‐DRB1*11:150 differs from HLA‐DRB1*11:01:01G by a single C to A substitution at nucleotide position 5580 in exon 2, resulting in an amino acid change from alanine to glutamic acid at position 74. HLA‐DRB1*14:145 differs from HLA‐DRB1*14:04 by a C to G substitution at nucleotide position 5511 in exon 2, resulting in an amino acid change from threonine to arginine at position 51.